Avaliação do nível de proficiência digital de professores do Instituto Federal do Tocantins - IFTO/Câmpus Palmas e Porto Nacional - Melo, Igor Barbosa (Universidade Federal do Tocantins, 2021)
Assessing an individual's digital proficiency level means measuring how competent they are in using Digital Information and Communication Technologies (TDIC) to benefit themselves and others. The intensity of digital skills can be measured by self assessment scales with specific criteria. The aim of this paper was to analyze the IFTO teacher proficiency level in digital technologies, based on the DigCompEdu “Check-In” self-assessment model developed by the EU Science Hub. Specifically, the delimitation of the research comprises analyzing the digital competences of teachers in the dimensions: professional, pedagogical and student. The methodological procedure used was a quantitative approach of exploratory and descriptive nature, using the content analysis structured by Bardin (1977) and statistical methods associated with the Theory of Sampling defined by Gil (2008). Participants in this research were 141 teachers from the Palmas and Porto Nacional campus of the IFTO, from different areas of knowledge. The theoretical framework addressed some education policies provided for in Brazilian legislation, emphasizing the promotion of ICT in the school environment. It is clear in the legal provisions mentioned throughout the dissertation, the attention of the Federal Government in enabling an initial or continued training of teachers of public schools, supported by a set of contemporary technologies. The results show that, globally, IFTO teachers have a moderate level of digital proficiency, at level B1 - Integrators. Participating audiences demonstrated greater weakness in the Teaching Skills of Teachers and Student Skills dimensions, with lower overall values on the DigCompEdu Check In scale. It was also concluded that being younger is not a condition for having a high level of digital proficiency. therefore, statistically, there are no significant differences when related to the variables “age” and overall average performance of teachers.